Effect of Educational Guidelines on Nurses’ Knowledge and Practices Regarding Ventilator Associated Pneumonia at Tertiary Care Hospital Lahore: Practices Regarding Ventilator-Associated Pneumonia - BB, Alvina; Afzal, Muhammad; Ali, Afsar (Pakistan Journal of Health Sciences, 2023)
Ventilator associated pneumonia (VAP) is a kind of pneumonia which develops in patients receiving mechanical breathing after 48 hours. One of the most prevalent nosocomial infections and the main factor in the high morbidity and mortality of intensive care units is ventilator-associated pneumonia (VAP). In order to prevent VAP, intensive care unit nurses are best equipped to use the available evidence-based measures (VAP). Objective: To determine the effect of educational Guidelines on the knowledge and practice of nurses regarding ventilator associated pneumonia. Methods: A Quasi-experimental one group pre-post, test was used conducted between January 2022 to May 2022 at a tertiary care hospital in Lahore, Pakistan, in the department of Medical intensive care unit and surgical intensive care unit. 36 registered nurses were selected by convenience sampling from tertiary care hospital Lahore according to inclusion and exclusion criteria. A structured questionnaire was used to evaluate the pre-post data that contained 20 MCQ-based knowledge questionnaire and 21 items containing practice checklist were used to check the practice level of nurses before and after guidelines-based educational intervention. Results: The results revealed a positive effect of educational guidelines on improving the nurse’s knowledge and practice about Ventilator-associated pneumonia (VAP). Mean ± S.D (7.78 ± 1.22; 15.86 ± 1.22) (8.94 ± 2.39; 17.39 ± 0.96) in post-test respectively with a statistically significant p-value (p-value <0.001). Conclusion: The education of nurses by educational guidelines has a positive effect on improving nurses’ knowledge and practice about Ventilator-associated pneumonia (VAP).